tan A -Sin A /sin2A
![{sin}^{2} {sin}^{2}](https://tex.z-dn.net/?f=+%7Bsin%7D%5E%7B2%7D+)
=
1+ CosA
Attachments:
![](https://hi-static.z-dn.net/files/dc5/0b8c7a91ca198559f8020c79d2c5bea3.jpg)
Answers
Answered by
4
Step-by-step explanation:
Given:-
(Tan A - Sin A)/ Sin^2 A
To show:-
(Tan A - Sin A)/ Sin^2 A = Tan A/(1+Cos A)
Solution:-
LHS:-
(Tan A - Sin A)/ Sin^2 A
=>[(SinA/Cos A)-Sin A]/ Sin^2 A
=>Sin A[(1/Cos A)-1)]/ Sin^2 A
=>Sin A [(1-Cos A)/Cos A] / Sin^2 A
On cancelling Sin A then
=>[ (1-Cos A)/Cos A] / Sin A
=>(1-Cos A)/( Sin A Cos A)
On multiplying both numerator and denominator by (1+CosA) then
=>(1-Cos A) (1+Cos A)/[Sin A Cos A (1+Cos A)]
=>(1-Cos^2 A)/[Sin A Cos A (1+Cos A)]
Since (a+b)(a-b)=a^2-b^2
We know that
Sin^2 A + Cos^2 A = 1
=> Sin^2 A/[Sin A Cos A (1+Cos A)]
On cancelling SinA
=>SinA/[ Cos A (1+Cos A)]
=>(Sin A/Cos A)/(1+Cos A)
=>Tan A/(1+Cos A)
=>RHS
LHS = RHS
Hence, Proved
Answer:-
(Tan A - Sin A)/ Sin^2 A = Tan A/(1+Cos A)
Used formulae:-
- (a+b)(a-b)=a^2-b^2
- Sin^2 A + Cos^2 A = 1
- Tan A = Sin A/ Cos A
Similar questions